Mechanism of Alkaline Earth Metal Amide Catalyzed Hydrogenation of Challenging Alkenes and Arenes - Qu, Zheng‐Wang; Zhu, Hui; Grimme, Stefan (ChemSusChem, 2024)
Recently, bulky alkaline earth (Ae=Mg, Ca, Sr, Ba) metal amide complexes AeN“2 (N”=N[Si(iPr)3]2) are shown to be active for catalyzing the hydrogenation of unactivated alkenes and arenes, presumably via the monomer N“AeH as catalyst. In sharp contrast, our extensive DFT calculations disclose that the double Ae−H−Ae bridged dimer (N”AeH)2 is kinetically more favorable in catalytic hydrogenation with H2, although rate‐limited by the initial hydrogenolysis of AeN“2 to form the monomer N”AeH. Extensive DFT calculations disclose that upon moderate heating alkaline earth metal amide AeN“2 reacts with H2 to form monomeric HAeN”, which can further dimerize into dimeric (HAeN“)2 as reactive catalyst for the hydrogenation of challenging alkene/arene C=C bonds with H2, thus providing deep mechanistic insights for metal amide based hydrogenation catalysis.